Chromosomal double-strand break repair in Ku80-deficient cells. - Liang, F (1996)
The x-ray sensitive hamster cell line xrs-6 is deficient in DNA double-strand break (DSB) repair and exhibits impaired V(D)J recombination. The molecular defect in this line is in the 80-kDa subunit of the Ku autoantigen, a protein that binds to DNA ends and recruits the DNA-dependent protein kinase to DNA. Using an I-SceI endonuclease expression system, chromosomal DSB repair was examined in xrs-6 and parental CHO-K1 cell lines. A DSB in chromosomal DNA increased the yield of recombinants several thousand-fold above background in both the xrs-6 and CHO-K1 cells, with recombinational repair of DSBs occurring in as many as 1 of 100 cells electroporated with the endonuclease expression vector. Thus, recombinational repair of chromosomal DSBs can occur at substantial levels in mammalian cells and it is not grossly affected in our assay by a deficiency of the Ku autoantigen. Rejoining of broken chromosome ends (end-joining) near the site of the DSB was also examined. In contrast to recombinational repair, end-joining was found to be severely impaired in the xrs-6 cells. Thus, the Ku protein appears to play a critical role in only one of the chromosomal DSB repair pathways.